Aripiprazole LAI two‐injection start in a 16 year‐old adolescent with schizophrenia - Virginio Salvi; Cristina Appignanesi; Brodinela Marpepa; Laura Orsolini; Umberto Volpe (Wiley, 2022)
Abstract Background Aripiprazole long‐acting injection (LAI) is approved for the treatment of schizophrenia in adults. Recently, Europe and Canada approved the use of the two‐injection start regimen: two separate injections of 400‐mg long‐acting aripiprazole along with a single 20‐mg dose of oral aripiprazole. Aripiprazole showed efficacy in the treatment of adolescents with acute schizophrenia in several controlled trials, leading to its approval for 13‐ to 17‐year‐old adolescents with schizophrenia by the EMA. However, the LAI formulation still remains off‐label in adolescents. Case presentation The patient was admitted to the General Psychiatry inpatient unit with a Positive and Negative Syndrome Scale (PANSS) total score of 136 and the Clinical Global Impression (CGI) score of 7. Aripiprazole was started and up‐titrated to 30 mg/d. After 3 weeks, the positive symptoms were significantly reduced; however, he still showed prominent negative symptoms. Clozapine 100 mg/d was added, and in the following 2 weeks, the patient appeared slightly more communicative and generally more aware of himself and the others. The PANSS total score decreased to 81. Due to poor insight, the patient was at‐risk not to take medications upon returning home; therefore, aripiprazole LAI was proposed. Since he urged to be discharged from the hospital, we opted for the two‐injection start. The medication was optimally tolerated, with no evidence of akathisia or other side effects. One month later, global functioning and illness insight improved; Positive and Negative Syndrome Scale score was 43 and CGI score 2. Conclusions Aripiprazole LAI showed good efficacy and tolerability in an adolescent with schizophrenia. The two‐injection start regimen was a safe and effective option.